Effects of Different Nitrogen Sources and Ratios to Carbon on Larval Development and Bioconversion Efficiency in Food Waste Treatment by Black Soldier Fly Larvae (Hermetia illucens) - Yan Lu; Shouyu Zhang; Shibo Sun; Minghuo Wu; Yongming Bao; Huiyan Tong; Miaomiao Ren; Ning Jin; Jianqiang Xu; Hao Zhou; Weiping Xu (Insects, 2021)
Biowaste treatment by black soldier fly larvae (BSFL, Hermetia illucens) has received global research interest and growing industrial application. Larvae farming conditions, such as temperature, pH, and moisture, have been critically examined. However, the substrate carbon to nitrogen ratio (C/N), one of the key parameters that may affect larval survival and bioconversion efficiency, is significantly less studied. The current study aimed to compare the nitrogen supplying effects of 9 nitrogen species (i.e., NH4Cl, NaNO3, urea, uric acid, Gly, L-Glu, L-Glu:L-Asp (1:1, w/w), soybean flour, and fish meal) during food waste larval treatment, and further examine the C/N effects on the larval development and bioconversion process, using the C/N adjustment with urea from the initial 21:1 to 18:1, 16:1, 14:1, 12:1, and 10:1, respectively. The food wastes were supplied with the same amount of nitrogen element (1 g N/100 g dry wt) in the nitrogen source trial and different amount of urea in the C/N adjustment trial following larvae treatment. The results showed that NH4Cl and NaNO3 caused significant harmful impacts on the larval survival and bioconversion process, while the 7 organic nitrogen species resulted in no significant negative effect. Further adjustment of C/N with urea showed that the C/N range between 18:1 and 14:1 was optimal for a high waste reduction performance (73.5–84.8%, p < 0.001) and a high larvae yield (25.3–26.6%, p = 0.015), while the C/N range of 18:1 to 16:1 was further optimal for an efficient larval protein yield (10.1–11.1%, p = 0.003) and lipid yield (7.6–8.1%, p = 0.002). The adjustment of C/N influenced the activity of antioxidant enzymes, such as superoxide dismutase (SOD, p = 0.015), whereas exerted no obvious impact on the larval amino acid composition. Altogether, organic nitrogen is more suitable than NH4Cl and NaNO3 as the nitrogen amendment during larval food waste treatment, addition of small amounts of urea, targeting C/N of 18:1–14:1, would improve the waste reduction performance, and application of C/N at 18:1–16:1 would facilitate the larval protein and lipid bioconversion process.